Biomedical laboratory science education: standardising teaching content in resource-limited countries - Wendy Arneson; Cathy Robinson; Bryan Nyary (AOSIS, 2013)
Background: There is a worldwide shortage of qualified laboratory personnel to provide adequate testing for the detection and monitoring of diseases. In an effort to increase laboratory capacity in developing countries, new skills have been introduced into laboratory services. Curriculum revision with a focus on good laboratory practice is an important aspect of supplying entry-level graduates with the competencies needed to meet the current needs. Objectives: Gaps in application and problem-solving competencies of newly graduated laboratory personnel were discovered in Ethiopia, Tanzania and Kenya. New medical laboratory teaching content was developed in Ethiopia, Tanzania and Kenya using national instructors, tutors, and experts and consulting medical laboratory educators from the United States of America (USA). Method: Workshops were held in Ethiopia to create standardised biomedical laboratory science (BMLS) lessons based on recently-revised course objectives with an emphasis on application of skills. In Tanzania, course-module teaching guides with objectives were developed based on established competency outcomes and tasks. In Kenya, example interactive presentations and lesson plans were developed by the USA medical laboratory educators prior to the workshop to serve as resources and templates for the development of lessons within the country itself. Results: The new teaching materials were implemented and faculty, students and other stakeholders reported successful outcomes. Conclusions: These approaches to updating curricula may be helpful as biomedical laboratory schools in other countries address gaps in the competencies of entry-level graduates.